2021
DOI: 10.3390/molecules27010091
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc as Potential Biomarkers of Mood Disorders and Pandemic Syndrome

Abstract: The diagnosis of affective disorders has been the subject of constant research by clinicians from all over the world for many years. Making an appropriate diagnosis among patients suffering from mood disorders is sometimes problematic due to the personality-changing nature of patients and the similarity in the clinical picture of episodes in affective disorders. For this reason, there is a need to develop rapid and effective methods of determining biological markers that differentiate these diseases. The resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Siwek et al reported that TBARS levels showed increased oxidative stress in the acute phase of bipolar disorder [7]. Microelements, including zinc and copper, which are involved in neuroinflammation [8], have been studied in mood disorders and copper levels were found to be low, while zinc levels were found to be higher in the control group [9]. The increase in peripheral inflammation marker levels and high incidence of some inflammatory and immune diseases in patients with BD support this hypothesis [10,11].…”
Section: Introductionmentioning
confidence: 92%
“…Siwek et al reported that TBARS levels showed increased oxidative stress in the acute phase of bipolar disorder [7]. Microelements, including zinc and copper, which are involved in neuroinflammation [8], have been studied in mood disorders and copper levels were found to be low, while zinc levels were found to be higher in the control group [9]. The increase in peripheral inflammation marker levels and high incidence of some inflammatory and immune diseases in patients with BD support this hypothesis [10,11].…”
Section: Introductionmentioning
confidence: 92%
“…Copper stimulates the production of ROS that are involved in oxidative stress that damages DNA, proteins, and lipids [225]. Further, it should be noted that ceruloplasmin, a major copper transporter in the human organism, was observed to be increased in patients suffering from mood disorders [226]. Although the role of ceruloplasmin in depression remains uncertain, elevated serum levels of ceruloplasmin may indicate the potential significance of copper ions in mood disorders [227][228][229].…”
Section: Coppermentioning
confidence: 99%
“…Zn, Mg and Cu were suggested to be involved in depressive disorders and proposed as a potential clinical marker for these conditions [36][37][38]. This was based on many reports indicating significant changes in blood levels of these elements during a depressive episode [18,39,40].…”
Section: Alterations In Element Concentrations In the Serum And Brainmentioning
confidence: 99%